Changes in Membrane Polar Lipid Fatty Acids of Seashore Paspalum in Response to Low Temperature Exposure - Cyril, J.; Powell, G. L.; Duncan, R. R.; Baird, W. V. (Crop science, 2002)
ABSTRACT Seashore paspalum (Paspalum vaginatum Sw.) is a warm‐season turfgrass, best known for its superior salt tolerance. Plants are subject to injury during winter conditions along the northern boundary of their zone of adaptation. New cultivars that are more tolerant to low temperatures are needed for use in the transition zone. Cold tolerance has been correlated with the degree of unsaturation in membrane lipid fatty acids. Unsaturated fatty acids are thought to aid in maintaining membranes in a fluid state necessary for biological functioning (homeophasic adaptation). The primary objective was to characterize fatty acid composition of membrane lipids in three genotypes differing in cold tolerance. A second objective was to investigate changes in fatty acid content in these genotypes during exposure to low temperatures. Cold‐treated plants were exposed to a 10‐h photoperiod at 8°/4°C day/night temperatures and light intensity of 250 μmol m−2 s−1 photosynthetic photon flux density for 3 wk. Rhizomes and crowns were harvested at 7‐d intervals. Total lipids were extracted and the polar lipids separated by thin‐layer chromatography. Fatty acids were identified by gas chromatography (GC) and mass spectroscopy. In all three genotypes, the two saturated fatty acids, palmitic acid and stearic acid, did not change during cold treatment. The triunsaturated linolenic acid increased significantly during low temperature exposure. The magnitude of change was greater in the finer‐textured and more cold‐tolerant PI 509018‐1 (‘SeaIsle1’) than in the intermediately cold‐tolerant ‘Adalayd’ or in the cold‐susceptible, coarse‐textured PI 299042. These findings suggest that accumulation of linolenic acid partly explains the differential response in their cold tolerance.